Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1095-8312.2007.00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scale patterns of shell and anatomy variability in land snails: the case of the Sicilian Marmorana (Gastropoda: Pulmonata, Helicidae)

Abstract: Certain major aspects of phenotypic diversity are still largely unexplained. When phenotypic patterns do not relate to habitat variables, fine analysis of morphological patterns and their distribution sheds light on the origin of diversity. Among invertebrates, snails are an ideal model for studying the roles of the neutral processes and selection involved in creating diversity. To understand patterns and processes of variability on different scales (regional: areas; local: sites), morphological variability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…The small shell aperture area has been interpreted as an adaptation to reduce water loss during aestivation (Santos and Monteirom 2001; Fiorentino et al 2008). Concerning spire index, Okajima and Chiba (2009) observed that shells with low-spired are better balanced and more adapted to locomotion on horizontal surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The small shell aperture area has been interpreted as an adaptation to reduce water loss during aestivation (Santos and Monteirom 2001; Fiorentino et al 2008). Concerning spire index, Okajima and Chiba (2009) observed that shells with low-spired are better balanced and more adapted to locomotion on horizontal surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the land snail species have been described simply on the basis of shell characteristics. During the XVIII century, naturalists had already observed variations in shell morphological patterns (Fiorentino et al 2008). However, it was only from observation that shell shape presents a bimodal distribution that functional aspects of shell morphology began to be investigated (Fiorentino et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Land snails are good organisms for studying phylogeography because they tend to preserve phylogeographical patterns (Pfenninger et al, 2007), due to their limited dispersal capacity and particular habitat requirements. Specifically, congeneric rock-dwelling species are seldom sympatric, more often they occupy small allopatric or parapatric ranges (Schilthuizen and Gittenberger, 1996;Welter-Schultes, 1998;Schilthuizen et al, 2004;Fiorentino et al, 2008a) with extremely limited gene flow between demes on a scale of only a few tens of metres (Schilthuizen and Lombaerts, 1994).…”
Section: Introductionmentioning
confidence: 99%